The Battle Against COVID-19 in Jordan: An Early Overview of the Jordanian Experience - Ala'a B. Al-Tammemi (Frontiers Media S.A., 2020)
Since the initial spark of the COVID-19 outbreak in December 2019, which was later declared by the World Health Organization (WHO) to be a global pandemic, all affected countries are implementing various preventive and control measures to mitigate the spread of the disease. The newly emerging virus brings with it uncertainty-not only regarding its behavior and transmission dynamics but also regarding the current lack of approved antiviral therapy or vaccines-and this represents a major challenge for decision makers at various levels and sectors. This article aims to provide an early overview of the COVID-19 battle within the Jordanian context, including general reflections and conclusions on the value of collaborative efforts in crises management.